Long QT syndrome: from channels to cardiac arrhythmias - Moss, Arthur J.; Kass, Robert S. (The Journal of Clinical Investigation, 2005)
Long QT syndrome, a rare genetic disorder associated with life-threatening arrhythmias, has provided a wealth of information about fundamental mechanisms underlying human cardiac electrophysiology that has come about because of truly collaborative interactions between clinical and basic scientists. Our understanding of the mechanisms that control the critical plateau and repolarization phases of the human ventricular action potential has been raised to new levels through these studies, which have clarified the manner in which both potassium and sodium channels regulate this critical period of electrical activity.